The effect of hippophae rhamnoides extract on oral mucositis induced in rats with methotrexate - Ozan Kuduban; Muhammed Recai Mazlumoglu; Selma Denktas Kuduban; Ertugrul Erhan; Nihal Cetin; Osman Kukula; Oguzhan Yarali; Ferda Keskin Cimen; Murat Cankaya
ABSTRACT Objective: To investigate the effect of HRE (Hippophae rhamnoides extract) on oral mucositis induced in rats with MTX. Material and Methods: Experimental animals were divided into groups as healthy (HG), HRE+MTX (HMTX), and control group, which received MTX (MTXC). HMTX group received 50 mg/kg HRE while MTXC and HG groups received equivolume distilled water with gavage once a day. After one hour of HRE and distilled water administration, HMTX and MTXC groups received a single dose of oral MTX 5 mg/ kg. This procedure was repeated for one month. Results: The levels of MDA, IL-1β, and TNF-α were found to be significantly higher in the cheek, lower lip, and tongue tissue of the animals receiving MTX, compared with HG and HMTX groups; however, these parameters were lower in the cheek and low lip tissue, and a milder damage ocurred in these tissues, compared with the tongue tissue in MTXC group. No histopathologic damage was observed in the cheek, lower lip, and tongue tissues of the rats treated with HRE. Conclusion: This findings indicate that HRE as a natural product is an important advantage compared with synthetic drugs for prophylaxis of oral mucositis developed due to MTX.